AIDS Updates - Recent Advances and New Perspectives 2021
DOI: 10.5772/intechopen.98418
|View full text |Cite
|
Sign up to set email alerts
|

Employment as a Social Determinant of HIV Care and Prevention Outcomes

Abstract: Advancements in HIV medicine has led to an increased desire and/or need to work for many people living with HIV. Despite the importance of work, relatively little attention has been devoted to specifically examining employment status as a social determinant of health. Unemployment/underemployment are associated with societal circumstances known to increase both the risk for acquiring and prevalence of HIV and other co-morbidity. Research indicates that being employed and use of vocational services is associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
(52 reference statements)
1
3
0
Order By: Relevance
“…Considering the role of employment as a social determinant of health, it is important to note that the majority of respondents, regardless of their phase of employment decision-making, reported a decrease in viral load, health risk behaviors, and drug/alcohol use since starting to work. This finding is consistent with other studies that have found support for the role that employment can play as a positive social determinant of health [ 2 , 39 ]. In a meta-analysis of research investigating the association between employment status and adherence to HIV medications, Nachega et al [ 40 ] suggest that employed individuals were 27% more likely than unemployed individuals living with HIV to adhere to antiretroviral medications.…”
Section: Discussionsupporting
confidence: 93%
“…Considering the role of employment as a social determinant of health, it is important to note that the majority of respondents, regardless of their phase of employment decision-making, reported a decrease in viral load, health risk behaviors, and drug/alcohol use since starting to work. This finding is consistent with other studies that have found support for the role that employment can play as a positive social determinant of health [ 2 , 39 ]. In a meta-analysis of research investigating the association between employment status and adherence to HIV medications, Nachega et al [ 40 ] suggest that employed individuals were 27% more likely than unemployed individuals living with HIV to adhere to antiretroviral medications.…”
Section: Discussionsupporting
confidence: 93%
“…The results obtained should help policymakers aiming to promote job-seeking strategies and policies on the working environment that are directed to people living with HIV, who still experience hardship compared with the general population. In some countries, certain vocational interventions and employment services, such as rehabilitation job centres [59] or micro-enterprise employment interventions [60], peer-employment models [61] or programmes consisting of integrated services that combine medical, employment, housing, and other psychosocial services [62], have improved health-related quality of life and reduced health-risk behaviours among people living with HIV [63][64][65]. In spite of those positive results, vocational rehabilitation programs for people living with HIV are commonly underfunded and in the early stages of development, exacerbating gaps in income supports for people living with HIV [63,66].…”
Section: Discussionmentioning
confidence: 99%
“…For those who were unemployed at the beginning of the pandemic, becoming employed had a positive effect on their HRQOL. This underscores the impact of employment as a social determinant of health for PLHIV (Conyers et al, 2021). Research exploring the relationship between employment and qual-COVID-19, Employment, and Quality of Life Among People Living With HIV Rehabilitation Counselors and Educators Journal ity of life of PLHIV indicates that transitions into employment help increase PLHIV's HRQOL due to greater financial independence and less social isolation.…”
Section: Employment and Health-related Quality Of Lifementioning
confidence: 99%